Correlation of Phonological Skills and Reading Skills in Children at Risk of Reading Difficulty - Syahida, Amaliya; Novianti, Ranti; Kurniawan, Citra (Angstrom Centre of Education, 2024)
This study aims to determine the correlation between phonological ability and reading ability in children at risk of reading difficulties, utilizing quantitative methods with a correlation research design to obtain accurate data on the relationship between these two variables. The results indicated a strong and positive relationship between phonological ability (Variable 1) and reading ability (Variable 2), with a Kendall tau correlation coefficient of 0.527 and a significance value of 0.002. The findings emphasize that enhancing phonological skills in children at risk of reading difficulties can significantly improve their reading ability. Consequently, it is recommended to implement early phonological skill development training and to conduct further research with larger samples and more diverse methodologies to reinforce these findings. This study aligns with Sustainable Development Goal 4 (SDG 4), which advocates for inclusive and equitable quality education and promotes lifelong learning opportunities for all.